Immune signatures predicting the clinical outcome of peanut oral immunotherapy: where we stand - Wanniang, Naphisabet; Boehm, Theresa-Maria; Codreanu-Morel, Françoise; Divaret-Chauveau, Amandine; Assugeni, Isabela; Hilger, Christiane; Kuehn, Annette (Frontiers in Allergy, 2023)
Peanut allergy is a rising health concern causing mild to severe anaphylaxis as well as reduced quality of life in patients and their families. Oral immunotherapy is an important therapeutic intervention that targets to reshape the immune system towards a higher threshold dose reactivity and in some patients, sustained unresponsiveness. From an immunological point of view, young patients, especially below the age of three, seem to have greatest chances for therapy success. So far, surrogate markers for therapy duration and response are evasive. We provide a comprehensive overview on the current state of literature regarding immune signatures evolving over the course of oral immunotherapy as well as baseline immune conditions prior to treatment start. Despite a paucity of research across different age groups, comparing clinical and immune traits in the first years of life vs later, there are promising insights available on immunological endotypes among peanut-allergic patients. Available data call for continued research to fill up the current knowledge gaps, possibly in an integrated manner, to design novel precision health approaches for advanced therapeutic interventions in peanut allergy.